Toll‐like receptor signalling cross‐activates the autophagic pathway to restrict Salmonella Typhimurium growth in macrophages. (26th August 2019) - Liu, Wei; Zhuang, Jing; Jiang, Yuanyuan; Sun, Jing; Prinz, Richard A.; Sun, Jun; Jiao, Xinan; Xu, Xiulong
Abstract: It has been long recognised that activation of toll‐like receptors (TLRs) induces autophagy to restrict intracellular bacterial growth. However, the mechanisms of TLR‐induced autophagy are incompletely understood. Salmonella Typhimurium is an intracellular pathogen that causes food poisoning and gastroenteritis in humans. Whether TLR activation contributes to S . Typhimurium‐induced autophagy has not been investigated. Here, we report that S . Typhimurium and TLRs shared a common pathway to induce autophagy in macrophages. We first showed that S . Typhimurium‐induced autophagy in a RAW264.7 murine macrophage cell line was mediated by the AMP‐activated protein kinase (AMPK) through activation of the TGF‐β‐activated kinase (TAK1), a kinase activated by multiple TLRs. AMPK activation led to increased phosphorylation of Unc‐51‐like autophagy activating kinase (ULK1) at S317 and S555. ULK1 phosphorylation at these two sites in S . Typhimurium‐infected macrophages overrode the inhibitory effect of mTOR on ULK1 activity due to mTOR‐mediated ULK1 phosphorylation at S757. Lipopolysaccharide (LPS), flagellin, and CpG oligodeoxynucleotide, which activate TLR4, TLR5, and TLR9, respectively, increased TAK1 and AMPK phosphorylation and induced autophagy in RAW264.7 cells and in bone marrow‐derived macrophages. However, LPS was unable to induce TAK1 and AMPK phosphorylation and autophagy in TLR4‐deficient macrophages. TAK1 and AMPK‐specific inhibitors blocked S . Typhimurium‐induced autophagy and xenophagy and increased the bacterial growth in RAW264.7 cells. These observations collectively suggest that activation of the TAK1–AMPK axis through TLRs is essential for S . Typhimurium‐induced autophagy and that TLR signalling cross‐activates the autophagic pathway to clear intracellular bacteria.